Powtoon-Based Learning Videos for Quality Elementary School Learning Outcomes (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Elementary school teachers in Cluster Dewi Kunthi Gunungpati Semarang still need to become skilled at creating learning videos. Due to misunderstanding, the teacher's educational background is not in educational technology, and the experience of creating learning videos is minimal. This service aims to provide enrichment, skills, evaluation, and creation of learning media. The material provided is Powtoon-based learning video creation skills. The learning media used are in the form of Powtoon-based learning videos and learning media modules. The use of learning media will make it easier for elementary school children to absorb the material. The method used is direct and guided learning. Community service activities were conducted for eight months, with eight training meetings and guidance. Direct learning is done by conditioning the teacher as a participant, following and conducting copyright training, and evaluating learning videos. Skills and evaluation materials are carried out in 6 meetings. Supervised is intended to carry out direct supervision, coaching, and training. The service results show that teachers master making Powtoon-based videos, as evidenced by the collection of learning videos. The service succeeded in increasing teacher skills in creating Powtoon-based learning videos.